Coe1 in Beta vulgaris L. Has a Tnp2-Domain DNA Transposase Gene within Putative LTRs and Other Retroelement-Like Features. (12th May 2008) - Kuykendall, David; Shao, Jonathan; Trimmer, Kenneth
Abstract : We describe discovery in Beta vulgaris L. of Coe1, a DNA transposase gene within putative long terminal repeats (LTRs), and other retrotransposon-like features including both a retroviral-like hypothetical gene and an Rvt2-domain reverse transcriptase pseudogene. The central DNA transposase gene encodes, in eight exons, a predicted 160-KDa protein producing BLAST alignments with En/Spm -type transposons. Except for a stop signal, another ORF encodes a Ty1-copia -like reverse transcriptase with amino acid sequence domain YVDDIIL. Outside apparent LTRs, an 8-mer nucleotide sequence motif CACTATAA, near or within inverted repeat sequences, is hypothetical extreme termini. A genome scan of Arabidopsis thaliana found another example of a Tnp2 -domain transposase gene within an apparent LTR-retrotransposon on chromosome 4.